Evolution of Category of the Other in Works of Tom Wolfe - E. A. Kulikov; V. G. Novikova (Научный диалог, 2024)
This article addresses the artistic embodiment of the category of the Other in the works of American journalist and writer Tom Wolfe. The study focuses on Wolfe’s early journalistic essays, compiled in collections published in the early 1960s, as well as his later novel “I Am Charlotte Simmons” (2004). These texts are separated by nearly the entire second half of the 20th century — a period marked by the emergence, flourishing, and decline of postmodernism. The aim of this work is to trace the diachronic evolution of the author’s understanding of the category of the Other, as represented in his early and late texts. The desire for otherness among young people in the first post-war decades signified a fundamental rejection of norms, rules, and laws in the name of rejecting all forms of totalitarianism, which led to the catastrophic destruction of humanity during World War II. As a journalist, Wolfe objectively and empathetically depicts the diverse lifestyles of a new generation. He illustrates the consequences of these emerging trends in his university novel written forty years later. The article demonstrates that this work presents the otherness of various status groups within the university community through a multi-layered conflict. However, these groups remain isolated and hostile towards one another. The abandonment of rational consciousness has led to the primitivization of individuality and the disintegration of education. The novel serves as a vivid illustration of the negative outcomes of postmodernism.